Anonymous
Anonymous asked in Science & MathematicsMathematics · 2 months ago

How does (-2/3)cot(2t)=0 solve to 2t = (pi/2) ?

If i get rid of the -2/3 i get cot(2t) =0 which is 1/tan(2t) = 0 which would make the whole thing zero. But taking just the denominator to equal zero would give tan(2t)=0 which gives 2t = 0 again??

1 Answer

Relevance
  • 2 months ago
    Favorite Answer

    Going back to cot(2t) = 0, write this as   cos(2t)/sin(2t)  = 0, which means that you just need  cos(2t) = 0. So there is cos(x) = 0?, when x = pi/2. Thus  2t = pi/2, and t = pi/4

    • Login to reply the answers
Still have questions? Get your answers by asking now.